HASIL BELAJAR KOGNITIF SISWA DENGAN PENERAPAN MODEL INSTRUKSIONAL DDFK (DEFINISI DESAIN FORMULASI KOMUNIKASI) PROBLEM SOLVING PADA SISWA KELAS X SAINS 1 MA DARUL HIKMAH PEKANBARU - Br Batubara, Emalia; Islami, Nur; Irianti, Mitri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to describe the cognitive learning outcomes of students using the DDFK (Definition Design Formulation Communication) learning model Problem Solving in class X Science 1 MA Darul Hikmah Pekanbaru. The benefit of this research is that teachers can be used as alternative learning models to help deliver material to be more innovative in teaching. Students are expected to be able to further enhance students' understanding and learning outcomes in physics. This type of research is a pre-experimental design research in the form of a one-shot case study. The subjects of the study were students of class X Science 1 with 32 female students at MA Darul Hikmah Pekanbaru. The research instrument used cognitive learning performance test questions about Work and Energy material. Data collection techniques in the form of providing learning outcomes tests conducted after learning. Data were analyzed descriptively by describing student cognitive learning outcomes. From the results of the study, the average student absorption is 70.75% with a good category and the effectiveness of learning with a good category. Seen from each learning meeting conducted, the highest average absorption capacity was at the first meeting, which was 84% with a good category, while the average absorption capacity was the lowest at the third meeting, which was 53% with a fairly good category.Key Words: Cognitive Learning Outcomes, DDFK Problem Solving, Work and Energy